2005
DOI: 10.7202/029355ar
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Commitment: Testing Two Theories

Abstract: L'étude du sentiment d'appartenance à l'entreprise a reçu une attention de plus en plus soutenue dans la documentation en ces derniers temps, et cela pour plusieurs raisons. D'abord, des employés fortement engagés peuvent fournir un apport plus utile que ceux qui le sont moins; l'appartenance à l'entreprise est souvent un meilleur remède au roulement de la main-d'oeuvre que la satisfaction au travail; enfin, elle est un indice de l'efficacité d'une entreprise. Le présent article porte sur l'étude de l'apparten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Our findings support this hypothesis and are consistent with Swailes (2000). An employee with a strong affiliation and committed to the organization would strive to generate new ideas (Amernic and Aranya, 1983) for new products or further work improvement. The findings confirmed that employee organizational commitment is an important factor perceived by both management and professionals to increase EI.…”
Section: Organizational Commitment and Employee Innovationsupporting
confidence: 88%
“…Our findings support this hypothesis and are consistent with Swailes (2000). An employee with a strong affiliation and committed to the organization would strive to generate new ideas (Amernic and Aranya, 1983) for new products or further work improvement. The findings confirmed that employee organizational commitment is an important factor perceived by both management and professionals to increase EI.…”
Section: Organizational Commitment and Employee Innovationsupporting
confidence: 88%
“…The concept employee commitment has been studied from various theoretical perspectives. According to Amernic and Aranya (1983) two major theoretical approaches have been employed in the writing on employee commitment: the exchange approach and the investment approach. These researchers have summarized previous researchers' explanation regarding these two approaches as follows: Firstly, the exchange theory refers that person's hierarchical responsibility relies upon their apparent equalization of remuneration utilities.…”
Section: Employee Commitmentmentioning
confidence: 99%
“…Becker contends that the greater number of side-bets, the greater the commitment of the individual. Over the years as the side-bet model was studied by various researchers, a side-bet index was established to include variables such as age, tenure, education, pay, gender, mobility, seniority, professional connections, organizational level, marital status, number of dependent children, and perceived job alternatives (Alluto, Hrebiniak, & Alonso, 1973;Amernic & Aranya;1983;Aranya & Jacobson, 1975;Ritzer & Trice, 1969;Shoemaker, Snizek, & Bryant, 1977).…”
Section: Historical Overview Of Organizational Commitmentmentioning
confidence: 99%